Entrepreneurial action: A bibliometric study on the international scientific production - Milena Abreu Ávila; Daniela Meirelles Andrade; Camila de Assis Silva; Vinícius Batista Gonçalves (Regepe Entrepreneurship and Small Business Journal, 2023)
Objective: To analyze the international scientific production in the field of entrepreneurial action. Method: To investigate the theme of entrepreneurial action, the bibliometric method was used to fulfill the desired purposes. In the operationalization of the research, articles available in the Web of Science and Scopus databases were included. The database selection procedure was carried out by analyzing the documents using the software: My EndNote Web, Microsoft Excel and VOSviewer. Results: It was possible to identify the scarcity of compassionate research on the subject, in addition to the fact that little is known about the emergence of an entrepreneurial action and how, in fact, this research axis can contribute to studies on entrepreneurship. Theoretical contributions: It was identified that there are promising studies on the subject that made possible the exchange of the concept of entrepreneurial action and the different areas of knowledge through the construction of a synthesis matrix. Relevance/originality: The field of entrepreneurial action is still incipient and requires greater efforts towards a theoretical and empirical development, in order to establish and contribute to the construction of a very limited and defined conceptual structure about the phenomenon. Contributions to management: Studies on entrepreneurial action are directly related to case studies that report the emergence of entrepreneurial actions in organizations, which emphasizes the concentration of work in the areas of management and business.